Augmented Reality For Critical Thinking In Elementary Science Education: Design And Validation Of A Solar System Learning Media - Ichwan (ASIAN PUBLISHER, 2026)
Critical thinking has become an essential competency in elementary science education, yet students often experience difficulties when learning abstract topics such as the solar system. This study aimed to design and validate an Augmented Reality (AR)-based learning media to facilitate elementary students’ critical thinking skills in solar system learning. The research employed a Research and Development (R&D) approach using the ADDIE model, involving expert validation, practicality testing, and effectiveness evaluation with sixth-grade students. The findings revealed that the developed media achieved a high validity score of 90.35%, indicating its suitability for classroom implementation. Practicality testing also demonstrated positive responses from both teachers and students, with scores categorized as highly practical. Furthermore, the media significantly improved students’ critical thinking skills, as reflected by an average N-Gain score of 0.67 and a significant difference between pre-test and post-test results. These findings suggest that AR can serve as an effective interactive learning environment that promotes critical thinking while supporting meaningful science learning in elementary education.